Influence of Interest Group Lobbying in India : Case for the Washington Style Business of Persuasion - Shreyaskar, Pankaj K. P.; Pandey, Mrinalini; Pathak, Pramod (Prabandhan: Indian Journal of Management, 2021)
Lobbying, even dyed-in-the-wool, and having acquired the status of an independent service industry in India, greatly steered in unstructured and opaque surroundings. The lobbying phenomenon at present in India is neither legal nor illegal. Of late, though several entities, including the interest groups, have lobbied for statutory foundations for this territory, their endorsement did not succeed. The present study traced and analyzed the socio-political environments of lobbying in India. It presented the policy implications and necessitated the essence of systematically studying lobbying from the rational perspectives qua a preconceived notion, as has been the approach at present in India. The paper attempted to identify the provenance of a new environment of business persuasion exactly on the lines of the Western societies in India. Further, the study demystified the masquerading techniques of the strategies adopted by the lobbyists to influence policy making. The article presented the raison d'être for regulating the lobbying industry in India. Besides, it also traced the evidence of presence of professional lobbyists in India. The paper highlighted, in brief, the institutional efforts made so far towards a new beginning of regulated lobbying in India.